Chapter Ostrogoths vs. Franks: Imagining the Past in the Middle Ages - Oppedisano, Fabrizio (Reti Medievali E-Book, 2022)
This introductory essay aims at highlighting some aspects concerning the connections between the Ostrogoths and Franks in the Middle Ages. To this end, cases from different contexts and chronologies have been examined: firstly, Giovanni Villani's chronicle, which conveys a polarized image of the Gothic and Carolingian worlds; and then some testimonies from the ninth century, that use the Ostrogothic model in connection with the present in a more complex and ambivalent manner. The various interpretations of the Gothic world are linked by a tendency to emphasize historical analogies, that leads to an overall and protracted disinterest in the specific forms of Ostrogothic society and in work that most documents it, Cassiodorus' Variae.